Comparison of clinical application of iRoot SP, GuttaFlow 2 and AH Plus root canal sealer - HU Jing (口腔疾病防治, 2020)
Objective The short-term clinical effects of two kinds of normal temperature flow root sealers (the calcium silicate-based sealer iRoot SP and the siloxane-based sealer GuttaFlow2) combined with single point filling technology and a frequently-used sealing agent (AH Plus) combined with continuous wave hot tooth filling technology were evaluated. Methods A total of 279 teeth (656 root canals) were randomly divided into three groups: the iRoot SP group, GuttaFlow2 group and AH plus group. We recorded the filling time of each root canal, collected a digital dental film to evaluate the filling effect of each root canal, and conducted a follow-up visit one week and one month after the operation to record the incidence of pain. We used SPSS 18.0 to analyze the above data. Results There was no significant difference in the root canal filling effect among the three groups (P > 0.05). There was no significant difference in the filling time between the iRoot SP group and the GuttaFlow2 group (P > 0.05), but the filling time was significantly shorter in the AH Plus group (P < 0.05). There was no significant difference in the postoperative pain between the iRoot SP group and the GuttaFlow2 group (P > 0.05), and the incidence of pain in the iRoot SP group and the GuttaFlow2 group was lower than that in the AH Plus group (P < 0.05). Conclusions GuttaFlow2 and iRoot SP combined with single point filling technology can save filling time and obtain good clinical effects compared with frequently-used hot tooth filling technology and the incidence of postoperative pain was low.